VILLAGE FUND ACCOUNTING: ACCOUNTABILITY BASED SIRI’ NA PACCE IN REALIZING SUSTAINABLE VILLAGE DEVELOPMENT - Andi Yustika Manrimawagau Bayan; Haliah; Andi Kusumawati (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstrac, Demands for accountability not only on central and local governments, but village governments also have same obligation in realizing accountable government. This study aims to see the accountability of village fund financial management in terms of siri'na pacce culture for sustainable village development. This research is a literature review, descriptive analysis. The result of this study is the implementation of village finances must be carried out effectively and efficiently, transparently and responsibly. To carry out this responsibility, agent directs all his abilities and expertise while sticking to cultural values of his region to produce quality financial information reports that can be trusted by the community. The contribution of cultural values in sustainable village development is the value of lempu' and ada' tongeng. The value of lempu' becomes a dimension of empowerment in the perception of responsibility which has a very meaning in relation to honesty. Ada' tongeng is seen as necessary as a code of conduct for the government to serve to maintain truth, validity and reliability in carrying out things. Abstrak, Dewasa ini tuntutan akuntabilitas tidak hanya pada pemerintah pusat maupun daerah saja, tetapi pemerintah desa juga memiliki kewajiban yang sama dalam mewujudkan pemerintahan yang akuntabel. Penelitian ini bertujuan melihat akuntabilitas pengelolaan keuangan dana desa dari sisi budaya siri’na pacce untuk pembangunan desa yang berkelanjutan. Penelitian ini merupakan literature review, bersifat analisis deskriptif. Hasil penelitian ini yaitu penyelenggaraan keuangan desa harus dilaksanakan secara efektif dan efisien, transparan dan bertanggung-jawab. Untuk melaksanakan tanggungjawab tersebut maka agen mengarahkan semua kemampuan dan keahliannya dengan tetap berpegang teguh pada nilai-nilai budaya daerahnya untuk menghasilkan laporan informasi keuangan yang berkualitas dan dapat dipercaya oleh masyarakat. Kontribusi nilai budaya dalam pembangunan desa yang berkelanjutan yakni nilai lempu’ dan ada’ tongeng. Nilai lempu’ menjadi dimensi pemberdayaan dalam persepsi tanggung jawab yang memiliki makna sangat dalam kaitannya dengan kejujuran. Ada’ tongeng dipandang perlu sebagai kode perilaku bagi pemerintah berfungsi untuk menjaga kebenaran, kevalidan dan keandalan dalam melaksanakan sesuatu.